Deploying Storage for Power Systems in Developing Countries : Policy and Regulatory Considerations - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
Energy storage is particularly well suited to developing countries’ power system needs. Developing countries frequently feature weak grids. These are characterized by poor security of supply, driven by a combination of insufficient, unreliable and inflexible generation capacity, underdeveloped or nonexistent grid infrastructure, a lack of adequate monitoring and controlequipment, and a lack of skilled human resources and adequate maintenance. In this context,energy storage can help enhance reliability. Deployed together with VRE, it can help displacecostly and polluting generation based on liquid fuels while increasing security of supply.Storage can also help defer and/or avoid the construction of new grid infrastructure